2018
DOI: 10.1371/journal.pone.0199840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naturally-produced lovastatin on feed digestibility, rumen fermentation, microbiota and methane emissions in goats over a 12-week treatment period

Abstract: Twenty male Saanen goats were randomly assigned to four levels of lovastatin supplementation and used to determine the optimal dosage and sustainability of naturally produced lovastatin from fermentation of palm kernel cake (PKC) with Aspergillus terreus on enteric methane (CH4) mitigation. The effects on ruminal microbiota, rumen fermentation, feed digestibility and health of animal were determined over three measuring periods (4-, 8- and 12-weeks) and the accumulation of lovastatin in tissues was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 49 publications
7
26
0
Order By: Relevance
“…Moreover, lovastatin can be produced by various white-rot fungi by controlling the culture conditions. The lovastatin has been demonstrated to effectively inhibit the HMG-CoA reductase enzyme in methanogenic bacteria by interfering with the assembly of isoprenoid chains needed for membrane phospholipid synthesis and thus selectively depressing the growth of methanogenic bacteria without affecting other ruminal microorganism community [12][13][14]. Our previous work found that purple field corn stover fermented with P. ostreatus and V. volvacea can be beneficial when fed as an alternative fiber feed to improve in vitro digestibility, rumen fermentation, and reduction of CH 4 production [12].…”
mentioning
confidence: 99%
“…Moreover, lovastatin can be produced by various white-rot fungi by controlling the culture conditions. The lovastatin has been demonstrated to effectively inhibit the HMG-CoA reductase enzyme in methanogenic bacteria by interfering with the assembly of isoprenoid chains needed for membrane phospholipid synthesis and thus selectively depressing the growth of methanogenic bacteria without affecting other ruminal microorganism community [12][13][14]. Our previous work found that purple field corn stover fermented with P. ostreatus and V. volvacea can be beneficial when fed as an alternative fiber feed to improve in vitro digestibility, rumen fermentation, and reduction of CH 4 production [12].…”
mentioning
confidence: 99%
“…The study also reported that animals relying on grass alone without supplementation still inadequate to ful ll energy and protein requirement to improve their growth performance [28]. According to Kahindi et al [47], crude protein content of dry mature tropical grasses is often below the minimum 8% that can provide minimum ammonia required for optimum microbial function in the rumen. Imbalance of energy and protein supply in buffalo ration could cause negative energy balance which lead to nutritional metabolic disease such as ketosis or acidosis [43].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the use of statins is reported to have adverse effects such as muscular pain, cramps and/or stiffness on skeletal muscles in humans [24]. We had previously reported that lovastatin effectively decreased methane production in goats [18]. Given the potential for myopathies at higher than recommended therapeutic doses the effects of naturally produced statins on the skeletal muscles of ruminants was a primary interest of ours.…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the Animal Care and Ethics Committee of the Universiti Putra Malaysia (UPM/IACUC/AUP-R0087/2015). Detail protocols of the study have been reported [18]. Briefly, twenty intact male Saanen goatsof 4–5 months old with average live weight of 26 ± 3.4 kg were used in the 12-week feeding trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation